Disease Vector Control Technology Innovations and Their Relationship to Public Health in Indonesia: A Review - Yusliani, Rita; Asrani, Wa Ode; Ocin (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Disease vectors are living organisms, especially from the arthropod group, which have an important role in the spread of various infectious diseases in Indonesia. Some commonly identified vector types include mosquitoes and flies, which are capable of being hosts for various pathogens. Globally, vector-borne disease transmission is estimated to contribute around 17% to the total number of infectious disease cases and is one of the main causes of high mortality rates. Objective: This article aims to explore various technological innovations in disease vector control efforts and their relation to public health. In addition, this article also focuses on evaluating the effectiveness of various methods that have been applied in reducing the risk of disease transmission. Method: The method used is literature review, which includes searching for articles from international and national journals through Google Scholar. A total of 25 relevant articles in the last five years were analyzed to delve deeper into disease vector control and environment-based policies. Results: The results of the review showed that a variety of control methods, including physical, biological, and chemical controls, had been applied effectively. However, there are challenges in the implementation of digital technology to improve the accessibility and quality of health services, especially in developing countries such as Indonesia. Conclusion: Disease vector control is a very important aspect in efforts to improve public health. With different types of vectors, such as mosquitoes, playing a role in the transmission of infectious diseases, there needs to be a comprehensive and integrated approach to managing these vector populations. Keywords: Control, Disease Vector, Public Health